Trichostomum basilatinervium (Pottiaceae, Bryophyta), a new species from the Mediterranean region of Chile - Rodríguez, Omar; Gallego, María Teresa; Larraín, Juan; Cano, María J. (Phytotaxa, 2026)
A new moss species, Trichostomum basilatinervium sp. nov., is described and illustrated from the Mediterranean region of Chile. Trichostomum basilatinervium is distinguished morphologically from other Trichostomum species by its imbricate leaves towards the stem base, appressed, sometimes contorted, with the apical ones incurved and crispate when dry, margins weakly denticulate or crenulate at the transitional area, lamina prolonging towards the mucro, costa broadest at base, in cross-section with 8–16 guide cells in two incomplete layers, usually with pairs of guide cells at the edges, and gymnostomous capsules. Drawings and light microscope photographs of the new species are provided, and possible confusion with other closely related taxa is discussed. Distribution of the new species is mapped.